Political philosophy a beginners' guide for students and politicians - Swift, Adam 1961- (Polity, 2019)
"This fourth edition of Adam Swift's highly readable introduction to political philosophy includes new material on nationalism, immigration and multiculturalism, as well as updated guides to further reading. Bringing political philosophy within the reach of all, this book provides us with tools to cut through the complexities of modern politics"--Provided by publisher.